Influence of pole and slot combinations on vibration and noise in external rotor axial flux in‐wheel motors. Issue 4 (1st April 2017) - Deng, Wenzhe; Zuo, Shuguang; Lin, Fu; Wu, Shuanglong
Abstract : This study provides a detailed finding of the influence of pole and slot combinations on vibration and noise in external rotor axial flux in‐wheel motors (AFWMs). Firstly, electromagnetic force exerted on the surface of permanent magnet is discussed and a two‐dimensional fast Fourier transformation is implemented to analyse its spatial distribution and frequency characteristics. Then, a multiphysics model is developed to predict the vibration and noise and figure out the main origin from the perspective of electromagnetism. The influence of pole and slot combinations on vibration and noise is also analysed via the proposed model. Finally, the effect of load on vibration and noise in AFWMs is further investigated. It turns out that zeroth spatial order of axial electromagnetic force is the main origin of vibration and noise in axial flux motors, which is quite different from radial flux motors. Moreover, AFWMs with larger lowest common multiple (LCM) of pole number (2 p ) and slot number ( Q s ) show lower noise level and for the motors that satisfy LCM(2 p, Q s ) ≠ 6 p, vibration and noise are greatly influenced by load. This study provides guidance for the design of low noise AFWMs.